Pengembangan Bahan Ajar Berbasis Lingkungan Pada Materi Teks Laporan Hasil Observasi Di Kelas X Smk Pelayaran Buana Bahari Medan - Susi Friska Sinaga (Jurnal Penelitian, Pendidikan dan Pengajaran: JPPP, 2020)
This research aims to determine: (1) the contruction of teaching material based environment on report text; (2) validating teaching material; and (3) the effectiveness of teaching material based environment on report text in grade X Pelayaran Buana Bahari Medan Vocational High School. This research use model of research and development Borg and Gall which adapted from Sanjaya. Data collection techniques in this research shows that: (1) material validation include content feasibility, presentation feasibility, and language feasibility shows the average percentation 92,93% in very good criteria; (2) design expert validation shows the average percentation 85,15% in very good criteria; (3) the effectiveness of teaching material shows the post test percentation 85,50% (higher than the pretest percentation 76, 17%).